Anthropology from the problem of demarcation: Mario Bunge’s work - Morales Inga, Sergio (2022)
The problem of demarcation consists in formulating the criteria that distinguish scientific from non-scientific knowledge. Although this problem integrates multiple disciplines, the social sciences are the least discussed —among them, anthropology. However, the works of Mario Bunge are an exception. Although most of his work covers the physical and natural sciences, Bunge devoted multiple texts to the social sciences. In relation to anthropology, Bunge proposed a definition that highlights its main epistemological and methodological features, recognizing it as a “basic science”. This allowed him to develop the demarcation problem by filling his void with respect to anthropology. Analyzing the literature on both domains, this paper synthesizes the Bungean work on anthropology according to the problem of demarcation in order to build bridges between two fields of knowledge that deserve more exchange than they have had.